Faktor-Faktor Keluarga dan Tingkah Laku Penyalahgunaan Dadah: Satu Kajian Perbandingan antara Penyalahguna Dadah dengan Bukan Penyalahguna Dadah - Al Hadi, H. M. Abdullah (Universiti Putra Malaysia Press, 1993)
The present study compares aspects of parent-child communication, parent-child nurturance, and family members involvement in drug abuse between drug abusers and non-drug abusers. Sample for the stud), were 191 drug abusers who were undergoing rehabilitation treatment at ('lUr Government Serenti Centres, and 191 non-drug abusers living in Kuala Lumpur. Two special instruments namely Communication and Parent-Child Interaction Rating Scales were used in this study. The study found significant differences between drug abusers and non-drug abusers in parent-child nurturance, parent-child communication, and family members involvement in drug abuse. Findings from this study have implications for drug abuse programmes in this country specifically those related to nurturance and parent-child communication, and parent behaviour model for children.